Perforin‐like protein PPLP2 permeabilizes the red blood cell membrane during egress of Plasmodium falciparum gametocytes. (4th April 2014) - Wirth, Christine C.; Glushakova, Svetlana; Scheuermayer, Matthias; Repnik, Urska; Garg, Swati; Schaack, Dominik; Kachman, Marika M.; Weißbach, Tim; Zimmerberg, Joshua; Dandekar, Thomas; Griffiths, Gareth; Chitnis, Chetan E.; et al.
Summary Egress of malaria parasites from the host cell requires the concerted rupture of its enveloping membranes. Hence, we investigated the role of the plasmodial perforin‐like protein PPLP2 in the egress of Plasmodium falciparum from erythrocytes. PPLP2 is expressed in blood stage schizonts and mature gametocytes. The protein localizes in vesicular structures, which in activated gametocytes discharge PPLP2 in a calcium‐dependent manner. PPLP2 comprises a MACPF domain and recombinant PPLP2 has haemolytic activities towards erythrocytes. PPLP2‐deficient [PPLP2(−)] merozoites show normal egress dynamics during the erythrocytic replication cycle, but activated PPLP2(−) gametocytes were unable to leave erythrocytes and stayed trapped within these cells. While the parasitophorous vacuole membrane ruptured normally, the activated PPLP2(−) gametocytes were unable to permeabilize the erythrocyte membrane and to release the erythrocyte cytoplasm. In consequence, transmission of PPLP2(−) parasites to the Anopheles vector was reduced. Pore‐forming equinatoxin II rescued both PPLP2(−) gametocyte exflagellation and parasite transmission. The pore sealant Tetronic 90R4, on the other hand, caused trapping of activated wild‐type gametocytes within the enveloping erythrocytes, thus mimicking the PPLP2(−) loss‐of‐function phenotype. We propose that the haemolytic activity of PPLP2 is essential for gametocyte egress due to permeabilization of the erythrocyte membrane and depletion of the erythrocyte cytoplasm.